Female dental students’ perceptions of patient safety culture: a cross sectional study at a middle eastern setting - Al-Surimi, Khaled (BMC Med Educ, 2018)
BACKGROUND: Patient safety is an integral part of all health care specialties, including dentistry. Dental students are exposed to patient safety culture during their clinical training. The aim of this study was to evaluate the perception of female students enrolled in dental degrees and dental hygiene programs towards patient safety culture and to determine its associated factors at a Middle Eastern setting. METHODS: This is a cross sectional study, based on a self-administered, English language questionnaire distributed by convenience among female dental students enrolled in two major Colleges of dentistry in Riyadh, Saudi Arabia. Participants had fulfilled at least one year of clinical training. Sample characteristics included the specialty and years of clinical training. Student’s perception was measured using the validated Safety Attitude Questionnaire (SAQ) that consists of 36 statements, distributed over six domains. Responses were rated on a five point Likert scale and the average positive response rate (APRR) was calculated. Binary logistic regression models were constructed to determine factors significantly associated with positive perceptions. RESULTS: The response rate of both student programs was 221/312(70.8%). Students of dental sciences and dental hygiene programs were 133(60.2%) and 88(39.8%) respectively. Almost 42% of students were in their 1st and 2nd years of clinical training. The APRR of: Team Work Climate domain was 54.4 ± 28.0, Safety Climate domain was 51.4 ± 29.7, Job Satisfaction domain was 64.5 ± 33.8, Stress Recognition domain was 56.2 ± 37.8, Perceived Management Support domain was 50.7 ± 37.7, and Working conditions was 55.3 ± 32.1. Female students in their 3rd and 4th year of clinical were adj.OR = 2.3[1.3–4.0] times more likely to have positive perception regarding the team work climate domain when compared to 1st and 2nd year clinical students, P = 0.005. At each of the six individual domains, the odds of having a positive perception were also significantly higher among dentistry students in comparison to dental hygiene students with a range of adj.OR 2.6–4.6. CONCLUSIONS: Apparently patient safety is a concern among female dental students enrolled in dental degree and dental hygiene programs. This requires more attention from the staff, dental college's leadership/management, and faculty/students. Perception of dental students towards patient safety culture is expected to improve with the increase of clinical training. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1415-8) contains supplementary material, which is available to authorized users.